Penggunaan Model Pembelajaran Problem Based Learning Untuk Meningkatkan Aktivitas dan Hasil Belajar Matematika Siswa Kelas VI Sekolah Dasar - Marsal Maret; Hendra Syarifuddin (Universitas PGRI Madiun, 2021)
This article aims to conceptually discuss the use of Problem Based Learning (PBL) learning models in student activities and learning outcomes in elementary schools, showing that with some efforts that have been made to improve learning activities and learning outcomes of grade VI students, but efforts have not been able to. running optimally, especially student activities that are decreasing, it is necessary to make efforts to improve the learning process, one of which is the Problem Based Learning (PBL) learning model. Based on observations, it shows that the Problem Based Learning (PBL) learning model has a good impact in terms of activities and learning outcomes, conceptually that the Problem Based Learning (PBL) learning model can be used as a model that is in line with improving the learning process which has a good impact on learning outcomes of students.